One‐year follow‐up of problem‐based task training for a child presenting cerebellar ataxia after brainstem glioma surgery: A single‐subject experimental study - Lee, Ye‐Seul; Oh, Duck‐Won (Physiotherapy research international : the journal for researchers and clinicians in physical therapy, 2021)
Background and purpose For the rehabilitation of patients with cerebellar ataxia, task training aids in achieving functional benefits. This study aimed to investigate the effects of problem‐based task training on balance and motor function in a child with cerebellar ataxia after brainstem glioma surgery. Methods This study used a single‐subject reversal design (A‐B) with a 1‐year follow‐up. A 5‐year old child with cerebellar ataxia due to a brain glioma completed problem‐based task training, including a 10‐step walk and return trial, walking while carrying an object, walking between parallel lines, and kicking a ball. Assessments were made using the Pediatric Balance Scale (PBS) and motor function tests (International Cooperative Ataxia Rating Scale (ICARS), Gross Motor Function Measure (GMFM), and Pediatric Evaluation of Disability Inventory (PEDI). Results During the intervention phase, the PBS score showed clinically and statistically significant improvement compared to the baseline score. The ICARS and GMFM scores improved by 10.53% and 3.56%, respectively, after the intervention. Furthermore, in the PEDI score, functional skills and caregiver assistance in the mobility domain increased by 7.58% and 5.02%, respectively, after the intervention. The improvements in all parameters were maintained or increased at further follow‐up phases. Conclusion These findings suggest that problem‐based task training has a positive effect on balance and motor function in a child with cerebellar ataxia after brainstem glioma surgery.